Effect of Pioneer Aeromedical Evacuation Program on Flight Medics’ Practices toward Emergency Casualties at Army Aviation Bases in Iraq (Indian Journal of Forensic Medicine & Toxicology, 2020)
Objective(s): The study aims to determination the effect of aeromedical evacuation program on flightmedics’ practices.Method: A pre-experimental design is carried in army aviation bases in Iraq, for the period of February 1st2019 to September 25th 2019. Non-probability “purposive” sample of (30) flight medics are selected fromarmy aviation bases. Non-probability “purposive” sample of (30) flight medics are selected from armyaviation bases. The questionnaire is composed of two main parts (demographic characteristics of the flightmedics, and the second part involves five domains which as (67) items concerning flight medics’ practicesregarding first aid of emergency casualties format, the researcher used SPSS version 20 to analyze the data.The reliability of the participant responses was estimated by alpha correlation (r) practice test was (r= 0.94),and content validity of the instrument was determined through a panel of (twenty-five) experts. Data wasanalyzed through the use of descriptive and inferential statistical analysis.Results: The results of the pretest for flight medics revealed that flight medics’ practices about five domainsof aeromedical evacuation program toward emergency casualties was moderate, while the posttest I and IIresults shows that flight medics’ practices was improved to high level because of the positive impact of theinstruction program, and there were significant association between the effectiveness of present program onflight medics’ practices and there level of education at P?0.05.Conclusion: The study concluded that the present program was effective on flight medics’ practices.Recommendation: The study recommended to increase the training courses for flight medics inside andoutside Iraq, and included the present program on their plan of training.